Eusebio de Cesarea y la controversia arriana. Una nueva interpretación del estallido de la crisis - Fernández Eyzaguirre, Samuel (Estudios eclesiásticos, 2024)
The article analyzes the role played by Eusebius of Caesarea in the first phase of the so-called Arian crisis. To this end, the Trinitarian theology of Eusebius and the two protagonists of the outbreak of the crisis are analyzed: the article examines the teaching of the bishop of Caesarea before the beginning of the controversy, then studies the theology of the presbyter Arius and the doctrine of the bishop Alexander. The analysis relies on the authentic writings of the authors. In particular, it avoids attributing to Arius the teachings that the polemical summaries assign to "the Arians." The last part of the article studies the convergences and divergences of these three authors. The conclusion proposes that the so-called Arian crisis was a conflict between two receptions of the Origenian tradition; one represented by Alexander and the other by Eusebius. Arius was not an original thinker, but a radical representative of a broader trend. The center of the theological discrepancy between these two tendencies was the coeternity of the Son (Alexander) or his posteriority prior to time (Eusebius). The proposed interpretation solves certain historical problems presented by traditional historiography.